Penentuan Maximum Acceptable Weight Limit (MAWL) Dengan Menggunakan Pendekatan Fisiologi - Rapiah Sarfa Marasabessy (Industrial Engineering Study Program, Pattimura University, 2012)
Manual Material Handling (MMH) is a material removal activitiey that performed manually. MMH has a high flexibility in handling the load - a light load if compared by using material handling equipment. However, MMH can cause injury identified in skeletal muscle (musculoskeletal disorders). To minimize the occurrence of injury in skeletal muscle, the National Institute of Occupational Safety and Health (NIOSH) recommends the imposition of an equation that is the Recommended Weight Limit. This equation is based on the data taken from American women workers in its use in Indonesia, the adjustment shall be made as there are differences in anthropometry, psychophysical and physiological differences between Indonesian and American. The purpose of this study was to determine the maximum load limit based on the anthropometry of Indonesian women workers. The approach used to determine the maximum load limits in this study is the physiological approach. Physiologically energy consumption based on the heart rate produced higher 56% -70% when compared to energy consumption based on NIOSH recommendations. This is because of the differences in anthropometric and age.